The Analysis of Community Based Agrotourism Customer Satisfaction in Yogyakarta - INDRAYANTI, Temy; JAMHARI, JAMHARI; MULYO, Jangkung Handoyo; MASYHURI, MASYHURI (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019DO - 10.14505//jemt.10.8(40).10, 2020)
This study aims to determine the level of customer satisfaction by Customer Satisfaction Index (CSI) and knowing what service attributes should be improved by IPA-Kano integration analysis. The research method used was a qualitative research on community based Salak Agrotourism in each category of Agrotourism, namely growing, developing and independent Agrotourism category. The measurement of visitor satisfaction uses the Service Quality (SERVQUAL) attributes (Reliability, Responsiveness, Assurance, Empathy and Tangibles). Based on the results of CSI, the services provided by the community based Salak Agrotourism manager are considered Satisfied in the Growing and Developing Agrotourism and Very Satisfied in the Independent Agrotourism. Priority of the attributes that should be improved are attributes that included in the Fatal, Defenseless Strategy Point, and Dusty Diamond category. The attributes included in the Fatal category are attributes that must be corrected immediately because they cause high dissatisfaction of service users. Attributes included in the Defenseless strategy point category are attributes that can be used as weapons to attack and defeat competitors. The attributes included in the Dusty Diamond category are attributes that if corrected can attract consumers' attention.